Modified new conjugate gradient method for Unconstrained Optimization - Zeyad M. Abdullah; Hameed M, Sadeq; Hisham M, Azzam; Mundher A. Khaleel (Tikrit Journal of Pure Science, 2019)
The current paper modified method of conjugate gradient for solving problems of unconstrained optimization. The modified method convergence is achieved by assuming some hypotheses. The statistical results demonstrate that the modified method is efficient for solving problems of Unconstrained Nonlinear Optimization in comparison with methods FR and HS